2020
DOI: 10.3390/sym12122109
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Systems and the Hidden Symmetries of the Kepler Problem

Abstract: The question of whether the solar distances of the planetary system follow a regular sequence was raised by Kepler more than 400 years ago. He could not prove his expectation, inasmuch as the planetary orbits are not transformed into each other by the regular polyhedra. In 1989, Barut proposed another relation, which was inspired by the hidden symmetry of the Kepler problem. It was found to be approximately valid for our Solar System. Here, we investigate if exoplanet systems follow this rule. We find that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…He found that the orbital parameters of the planets in our solar system follow this rule to a good approximation. In a recent work, one of us investigated if the observed data of some selected exoplanetary systems follow the symmetry-governed transformations [7]. A remarkable agreement was found.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…He found that the orbital parameters of the planets in our solar system follow this rule to a good approximation. In a recent work, one of us investigated if the observed data of some selected exoplanetary systems follow the symmetry-governed transformations [7]. A remarkable agreement was found.…”
Section: Introductionmentioning
confidence: 87%
“…In [7], only a few quintuple-planet or bigger systems were taken into consideration. Here, our exploration covers as many cases as possible by looking at all exoplanetary systems having four or more planets.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 3 more Smart Citations